Effect of Cardinium Infection on the Probing Behavior of Bemisia tabaci (Hemiptera: Aleyrodidae) MED. Issue 3 (19th June 2021) - Ying, Liu; Baiming, Liu; Hongran, Li; Tianbo, Ding; Yunli, Tao; Dong, Chu
Abstract: Facultative endosymbionts can affect the growth, physiology, and behavior of their arthropod hosts. There are several endosymbionts in the invasive whitefly Bemisia tabaci Mediterranean (MED, Q biotype) that influence host fitness by altering stylet probing behavior. We investigated the probing behavior of B. tabaci MED infected with the facultative endosymbiont Candidatus Cardinium hertigii ( Cardinium (Sphingobacteriales: Flexibacteraceae)). We generated genetically similar Cardinium -infected (C *+ ) and uninfected (C - ) clonal sublines and analyzed the probing behavior of newly emerged adult on cotton (Malvales: Malvaceae), Gossypium hirsutum L., using electropenetrography (EPG). The C - subline demonstrated a longer duration of E2 (2.81-fold) and more events of E2 (2.22-fold) than the C *+ subline, indicating a greater level of sustained ingestion of plant phloem. These findings provide insight into the fitness costs (fitness of a particular genotype is lower than the average fitness of the population) of the Cardinium -infected B. tabaci .